Thermal Efficiency Analysis of SkyFuel's Advanced, Large-aperture, Parabolic Trough Collector. (May 2015) - Hoste, G.; Schuknecht, N.
Abstract: SkyFuel has empirically established the thermal efficiency of the SkyTrough ® DSP : an advanced, low-cost parabolic trough collector recently developed by SkyFuel, Inc., and funded in part by DOE grant DE-EE0003584.000. A full-scale demonstration module has been built at SkyFuel's headquarters in Colorado for the purpose of comprehensive performance and efficiency testing. This testing is complete, andincludes the analysis of the collector's optical laser intercept, heat loss of the molten salt-compatible receivers, optical efficiency while tracking the sun, operation with molten salt, and molten salt freeze recovery. Complete results are presented herein for the SkyTrough ® DSP parabolic trough.